A Narrative Review on Garbhajanya Vishamayata: The Pregnancy Induced Hypertension : Life Science-Pharmaceutics - Kakde, Maithli; S. Pargaonkar, Akshay; Jibkate, Bhagyashree; Deshpande, Mayuri (International Journal of Life Science and Pharma Research, 2023)
Gestation, also known as Pregnancy, is the period during which one or more progeny develops inside a woman's womb. It is a crucial stage for a woman as several physiological changes occur during this period in her body. Now a day's, Pregnancy induced hypertension (PIH) is becoming the primary cause of maternal and prenatal mortality and morbidity. The prevalence of PIH is 2-8% of all pregnancies. In India, PIH incidence is higher in primiparae than in multipara. Therefore, finding all possible measures to prevent this disease is essential. In Ayurveda, Acharya Harit explains these conditions under Garbhinivyadhi. Garbhajanya Vishamayata is a condition in which hypertension develops after 20 weeks of gestation. Therefore, it is a primary concern during Pregnancy and can be prevented by early detection and appropriate treatment. Our Objective isto gain knowledge of ayurvedic aspects of Pregnancy induced hypertension, its prevention and treatment. This review is emphasized the ayurvedic aspects of Pregnancy induced hypertension. Detailed information was gathered by studying related classical texts of Ayurveda, research articles and websites. Collected data was later compiled, analyzed and discussed. This review concluded that by following Antenatal care(manumatic paricharya), Dos and don'ts (Pathyapathya), this disease can be prevented and treated effectively with safe motherhood and a healthy child. Keywords: , ,, ,